The clinical use of longitudinal bio-electrical impedance vector analysis in assessing stabilization of children with severe acute malnutrition. Issue 4 (April 2021) - Bourdon, Céline; Bartels, Rosalie H.; Chimwezi, Emmanuel; Kool, Jacintha; Chidzalo, Katherine; Perot, Lyric; Brals, Daniella; Bandsma, Robert H.J.; Boele van Hensbroek, Michael; Voskuijl, Wieger P.
Summary: Background & aims: Severe Acute Malnutrition (SAM) in children is determined using anthropometry. However, bio-electrical impedance (BI) analysis could improve the estimation of altered body composition linked to edema and/or loss of lean body mass in children with SAM. We aimed to assess: 1) the changes in BI parameters during clinical stabilization and 2) whether BI parameters add prognostic value for clinical outcome beyond the use of anthropometry. Methods: This prospective observational study enrolled children, aged 6–60 months, that were admitted at Queen Elizabeth Central Hospital in Blantyre, Malawi, for complicated SAM (i.e., having either severe wasting or edematous SAM with a complicating illness). Height, weight, mid-upper arm circumference (MUAC), and BI were measured on admission and after clinical stabilization. BI measures were derived from height-adjusted indices of resistance (R/H), reactance (Xc/H), and phase angle (PA) and considered to reflect body fluids and soft tissue in BI vector analysis (BIVA). Results: We studied 183 children with SAM (55% edematous; age 23.0 ± 12.0 months; 54% male) and 42 community participants (age 20.1 ± 12.3 months; male 62%). Compared to community participants, the BIVA of children with edematous SAM were short with low PA and positioned low on the hydration axis which reflects severe fluid retention. In contrast, children with severe wasting had elongated vectors with a PA that was higher than children with edematous SAM but lower than community participants. Their BIVA position fell within the top right quadrant linked to leanness and dehydration. BIVA from severely wasted and edematous SAM patients differed between groups and from community children both at admission and after stabilization (p < 0.001). Vector position shifted during treatment only in children with edematous SAM (p < 0.001) and showed a upward translation suggestive of fluid loss. While PA was lower in children with SAM, PA did not contribute more than anthropometry alone towards explaining mortality, length of stay, or time-to-discharge or time-to-mortality. The variability and heterogeneity in BI measures was high and their overall added predictive value for prognosis of individual children was low. Conclusions: BIVA did not add prognostic value over using anthropometry alone to predict clinical outcome. Several implementation challenges need to be optimized. Thus, in low-resource settings, the routine use of BI in the management of pediatric malnutrition is questionable without improved implementation.